CD8+ T-cell immunity in chronic inflammatory demyelinating polyradiculoneuropathy - Schneider-Hohendorf, T; Schwab, N; Uçeyler, N; Göbel, K; Sommer, C; Wiendl, H (Neurology, 2012)
Chronic inflammatory demyelinating polyradiculopathy (CIDP) is a common, but often misdiagnosed disease of the peripheral nervous system with assumed autoimmune pathogenesis. While current concepts of CIDP postulate a pathogenetic role of B cells and (auto)antibodies, the relevance of CD8 T cells present in the biopsies is still elusive. Thus, we asked whether nervous tissue infiltrating and blood-derived lymphocytes in CIDP are clonally expanded to evaluate the involvement of T cells in the pathogenesis of the disease. We characterized the clonal composition of the T-cell receptor repertoire in sural nerve biopsies (n = 25) and matching peripheral blood (n = 12) of patients with CIDP using PCR-based CDR3 spectratyping and subsequent DNA sequencing. As controls we used inflammatory myopathies (dermatomyositis, inclusion body myositis) and nonpathologic control biopsies. Immunohistochemistry was employed to visualize expanded CD8+ T-cell populations in sural nerve biopsies. In contrast to controls, T cells in CIDP biopsies showed strong monoclonal and oligoclonal restrictions in their T-cell receptor repertoire. Strikingly, clonal expansions found in the biopsies were reflected in the CD8+ T-cell pool of patients' peripheral blood. Clones overlapping between blood and biopsy could be confirmed by CDR3 sequencing. Finally, the predominance of expanded nerve-infiltrating CD8+ T-cell clones was visualized by immunohistochemistry. Together, these data provide strong evidence for an antigen-driven, major histocompatibility complex class I restricted, CD8+ T-cell-mediated attack against peripheral nerve tissue components contributing to the pathogenesis of CIDP.